Deep learning based decoding of single local field potential events - Schilling, Achim; Gerum, Richard; Böhm, Claudia; Rasheed, Jwan; Metzner, Claus; Maier, Andreas; Reindl, Caroline; Hamer, Hajo; Krauß, Patrick (NeuroImage, 2024)
How is information processed in the cerebral cortex? In most cases, recorded brain activity is averaged over many (stimulus) repetitions, which erases the fine-structure of the neural signal. However, the brain is obviously a single-trial processor. Thus, we here demonstrate that an unsupervised machine learning approach can be used to extract meaningful information from electro-physiological recordings on a single-trial basis. We use an auto-encoder network to reduce the dimensions of single local field potential (LFP) events to create interpretable clusters of different neural activity patterns. Strikingly, certain LFP shapes correspond to latency differences in different recording channels. Hence, LFP shapes can be used to determine the direction of information flux in the cerebral cortex. Furthermore, after clustering, we decoded the cluster centroids to reverse-engineer the underlying prototypical LFP event shapes. To evaluate our approach, we applied it to both extra-cellular neural recordings in rodents, and intra-cranial EEG recordings in humans. Finally, we find that single channel LFP event shapes during spontaneous activity sample from the realm of possible stimulus evoked event shapes. A finding which so far has only been demonstrated for multi-channel population coding.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Auditory cortex; Auditory neuroscience; Auto-encoder; Deep learning; Embeddings; Intracranial EEG (iEEG); Local field potentials; Speech perception; Stereotactic EEG (sEEG)